Malaysia : Financial Sector Assessment Program Monetary Liquidity Frameworks-Technical Note. (IMF Staff Country Reports; Country Report ;, 2014)
This technical note on Monetary Liquidity Frameworks on Malaysia's inflation analyzes that it has returned to a more stable path, after some wider fluctuations before and during the global financial crisis. On the liability side, Malaysian banks' liquidity is based largely on deposits. The increase in foreign reserves at the Central Bank is a major driver of the growth of the Bank Negara Malaysia's balance sheet. Monetary operations with Islamic banks are carried out through specific Shariah-compliant instruments.